Tingkat Pemahaman Siswa Terhadap Bullying pada Siswa Kelas X SMA Negeri 96 Jakarta - Kezia Dhiya Fitronella; Dwi Dasalinda (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This study aims to measure students' understanding of bullying among 10th-grade students at SMA Negeri 96 Jakarta. Bullying is a serious issue that can affect students' mental and physical health, making a good understanding of bullying crucial for its prevention and resolution. The research method used is a descriptive survey with a questionnaire as the data collection instrument. The questionnaire covers various aspects of bullying, including its definition, types of bullying, negative impacts, and prevention and handling strategies. The sample in this study consists of 52 10th-grade students. The results show that most students have a fairly good understanding of the definition and types of bullying. Although the students' basic understanding of bullying is quite good, further efforts are needed in education and raising awareness about the impacts and handling of bullying. The recommendation of this study is to implement comprehensive anti-bullying education programs in schools to create a safe and supportive learning environment for all students.